THE IMPLEMENTATION OF BLOOM’S REVISED TAXONOMY IN TEACHER’S QUESTIONS IN TEACHING ENGLISH AT SENIOR HIGH SCHOOL - Maya Anggriani; Johannes Jefria Gultom (Universitas Negeri Medan, 2021)
The present study entitled “The Implementation of Bloom’s Revised Taxonomy in Teacher’s Questions in Teaching English at Senior High School” focuses on describing the categorization of teacher’s questions according to the theory proposed by Wilen (1991) and Anderson and Krathwol (2000). The main purpose of the study is investigating and analyzing cognitive level of teacher’ questions based on the mentioned theory, and additionally the technique of questioning used. The data were collected through the observation from the three lesson videos selected on Youtube and were transcribed. The researcher only focuses on collecting the teacher’s question utterances from grade of X and XI senior high school in the topic of descriptive and biography text. The results showed that the teacher 1 used 8 techniques out of 9 techniques of questioning, teacher 2 and teacher 3 used 6 techniques of questioning. The three teachers similarly didn’t use T9 technique, and frequently used T8 technique. There are 4 cognitive levels used by teacher 1 and teacher 2 those are remembering (C1), understanding (C2), analyzing (C4), and creating (C6). In the side of teacher 3 only used 2 cognitive levels in questioning the students, those are remembering (C1) and understanding (C2). The three teachers frequently asked questions in the level of remembering (C1) respectively 69% from video 1, video two is 43%, and video 3 is 70%.Keywords: Teacher's Question, Bloom’s Revised Taxonomy, Techniques of Questioning.